Technological Improvement of Brined Black Table Olives Processed Using Two-Phase and Single-Phase Methods Under Slight CO2 Pressure and Low Salt Content - Biagi Angelo Zullo; Gino Ciafardini (Foods)
The aim of this work was to study the fermentation of black table olives under slightly pressurized CO2 (spCO2). The olives were marinated in brine with a low salt content and processed using both the traditional two-phase method and a new single-phase method. SpCO2 is a new technical tool, positively tested in previous studies on the production of low-salt table olive, as a third barrier to microbial growth in brine. The tests performed with the cultivar Leccino, using a brine acidified with 0.5% (w v−1) citric acid and enriched with 0%, 3%, and 6% (w v−1) NaCl, showed the absence of bacteria and molds in the brine from the first days of incubation. Fermentation was governed by six yeast species, mainly represented by Candida boidinii and Saccharomyces cerevisiae, with a maximum total number of 6.30 Log CFU mL−1 and 4.28 Log CFU mL−1 in the brine with 3% and 6% (w v−1) NaCl, respectively. The best debittering results were obtained when the olives were processed in the presence of spCO2 with the single-phase method, using brine with 6% (w v−1) NaCl, validating the important role played by spCO2 in the production of low-salt black table olives.